The Relationship between Handgrip Strength and Balance in the Pelangi Nusantara Elderly Women's Community - Bintang Bimo; Noortje Anita Kumaat; Himawan Wismanadi; Muhammad Dzul Fikri (Indonesian Journal of Kinanthropology (IJOK), 2026)
Background: As older adults age, they experience a decrease in muscle mass and strength (sarcopenia), which increases the risk of falls and impacts morbidity, mortality, and quality of life. However, evidence on the relationship between handgrip strength and balance, as measured using the timed up and go test, in community-dwelling older adults is still limited, particularly in Indonesia. Thus, the purpose of this study is to examine the relationship between handgrip strength and balance in older adults. Methods: This study used a cross-sectional study design. The sample size in this study was 35 female individuals who met the inclusion and exclusion criteria. The handgrip strength test used a handgrip dynamometer. Meanwhile, the balance test was measured with a time up and go test. Data normality analysis used the Shapiro Wilk test method (p-value > 0.05), and Pearson correlation to analyze the relationship between two variables (p-value < 0.05). Results: There was a significant negative correlation between the average right HGS (16.63 kg) and TUG (p-value 0.001 and r-value -0.600) and the average left HGS (15.39 kg) and TUG (p-value 0.002 and r-value -0.513). Conclusions: :  This study shows that dominant handgrip strength in community-dwelling older women is significantly correlated with balance and mobility. These findings expand the evidence in Indonesia that dominant handgrip strength has the potential to be used as an early screening indicator for functional mobility in older adults.